2020
DOI: 10.3389/fevo.2020.576692
|View full text |Cite
|
Sign up to set email alerts
|

Bumble Bees (Hymenoptera: Apidae) Respond to Moth (Lepidoptera: Noctuidae) Pheromone Components, Leading to Bee Bycatch in Monitoring Traps Targeting Moth Pests

Abstract: Semiochemical-baited traps are commonly used to monitor moth pests and inform management decisions. Unfortunately, bee pollinators can be unintentionally captured, which reduces monitoring system efficiency and may negatively impact pollinator biodiversity and pollination services. We assessed the abundance and diversity of wild bees captured in semiochemical-baited traps designed to capture cutworm and armyworm (Lepidoptera: Noctuidae) pests in North America. Green Unitraps were baited with semiochemicals inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Traps baited with food bait lures based on fermented by-products had a low pollinator by-catch; however, the addition of a floral volatile increased Bombus spp. by-catch [ 17 ]. Food bait lures based on microbial volatile organic compounds may be especially suitable for monitoring cutworm and armyworm moths because pollinators do not appear to be attracted to these compounds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Traps baited with food bait lures based on fermented by-products had a low pollinator by-catch; however, the addition of a floral volatile increased Bombus spp. by-catch [ 17 ]. Food bait lures based on microbial volatile organic compounds may be especially suitable for monitoring cutworm and armyworm moths because pollinators do not appear to be attracted to these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, food bait lures based on microbial volatile organic compounds can be further developed to attract redbacked cutworm moths and potentially other cutworm and armyworm pests in field crops, and have a minimum negative effect on native pollinator by-catch [ 17 ]. Although food bait lures capture lower numbers of targeted moths compared to sex pheromone-baited traps, both males and females of multiple cutworm species are attracted to AAMB lure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bumble bees were collected within pest monitoring traps that were placed by state cooperators in agricultural fields across diverse regions in the USA as part of early-detection surveys for invasive lepidopterans following Spears et al, (2016) and U.S. Department of Agriculture, Animal and Plant Health Inspection Service, Cooperative Agricultural Pest Survey approved methods for pest surveillance (CAPS, 2022). Previous research identified that bumble bees are attracted to pest monitoring traps and suggested that these captures be used to advance knowledge of biodiversity, population fluctuations, and other ecological objectives (Buchholz et al, 2011; Spears and Ramirez, 2015; Sipolski et al, 2019; Whitfield et al, 2019; Grocock et al, 2020; Grocock and Evenden, 2020; Parys et al, 2021; Spears et al, 2016, 2021; Christman et al, 2022a).…”
Section: Methodsmentioning
confidence: 99%